INTERNAL LIMITING MEMBRANE FLAP TECHNIQUE IN THE MANAGEMENT OF PRIMARY LARGE MACULAR HOLE IN JEC PRIMASANA HOSPITAL: ANATOMIC AND VISUAL OUTCOME - santy Kusumawaty; Soedarman Sjamsoe; W.Girsang.Elvioza; Soefiandi Soedarman; King Hans Kurnia (Fakultas Kedokteran Universitas Alkhairaat, 2025)
ABSTRACT This descriptive study aimed to investigate the effectiveness of the internal limiting membrane (ILM) flap technique in treating primary large macular holes (MHs) in patients at JEC Primasana. A total of 24 patients with large MH (>400 um diameter) were included in this study. Patient demographics, including gender, age, laterality, tamponade used, lens status, macular hole index (MHI) and BCVA (logMAR) were recorded. Changes in visual acuity before and after treatment were assessed using the Wilcoxon test. Differences in MHI by closure type were analyzed using the Mann-Whitney test. The correlation between MHI and postoperative visual acuity was evaluated using Spearman's rank correlation. The main outcome measures were the anatomical MH closure and final BCVA (logMAR). This study found that the ILM flap technique resulted in significant improvements in anatomy and visual acuity post-treatment. A total of 19 patients (79.2%) had MH closure and a mean improvement in BCVA (logMAR) of 1.02±0.63. The correlation between MHI and postoperative visual acuity in the closure group was positive, the higher the MHI, the better the BCVA.The ILM flap technique showed fairly good effectiveness in improving functional and anatomical outcomes in patients with large MH at JEC Primasana.